2018
DOI: 10.3748/wjg.v24.i27.2921
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green-based fluorescence imaging in visceral and hepatobiliary and pancreatic surgery: State of the art and future directions

Abstract: In recent years, the use of fluorescence-guided surgery (FGS) to treat benign and malignant visceral, hepatobiliary and pancreatic neoplasms has significantly increased. FGS relies on the fluorescence signal emitted by injected substances (fluorophores) after being illuminated by ad hoc laser sources to help guide the surgical procedure and provide the surgeon with real-time visualization of the fluorescent structures of interest that would be otherwise invisible. This review surveys and discusses the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 65 publications
1
65
0
3
Order By: Relevance
“…In this systematic review, we identified seven studies using fluorescence endoscopy to assess and evaluate tumor invasion, detect neoplasms, adenomas and esophageal varices. Although fluorescence endoscopy was first described many years ago, this method with interesting results has become even more promising for therapeutic and diagnostic purposes with the recent advances within the field of fluorescence-guided surgery and cancer-specific imaging[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this systematic review, we identified seven studies using fluorescence endoscopy to assess and evaluate tumor invasion, detect neoplasms, adenomas and esophageal varices. Although fluorescence endoscopy was first described many years ago, this method with interesting results has become even more promising for therapeutic and diagnostic purposes with the recent advances within the field of fluorescence-guided surgery and cancer-specific imaging[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a low-cost molecule, easy to use, widely available and with negligible toxicity [19]. The use of ICG uorescence in abdominal surgery has been introduced in recent years and represents a common tool for perfusion evaluation, extrahepatic bile duct anatomy, lymph node navigation and liver surgery [20][21][22]. ICG binds primarily to serum albumin and other serum globulins such as alpha1-lipoprotein, and then it circulates behaving like a macromolecule [23].…”
Section: Discussionmentioning
confidence: 99%
“…Following intravenous administration of the ICG dye, the concentration of the dye will fall exponentially. Measurements of ICU clearance are performed in serial blood samples but can also be determined noninvasively, through pulse dye densitometry using an optical sensor placed at the fingertip [37, 38]. The use of this technology was found to be the best discriminating preoperative test for evaluating hepatic functional reserve in patients diagnosed with HCC [36].…”
Section: Indocyanine Green Fluorescence Imagingmentioning
confidence: 99%